2008
DOI: 10.1007/s00468-008-0267-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental, root, and microbial biomass characteristics in soil respiration in temperate secondary forests of Northeast China

Abstract: For secondary forests, the major forest resources in China (accounting for more than 50% of the national total), soil respiration (R S ) and the relationship between R S and various biotic/abiotic factors are poorly understood. The objectives of the present study were to examine seasonal variations in soil respiration during the growing season, and to explore the factors affecting the variation in soil respiration rates for three forest types (Mongolian oak, Manchurian walnut and mixed forests) of temperate se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…Additionally, the amount of rainfall that actually reached the soil was lower in control plots due to the higher forest crown interception during light rainfall events (Bao et al, 2004); for example, over 60% of the annual rainfall was intercepted by the pine canopy (Bao et al, 2004). Our observation of lower soil moisture and lower R s in the control stands than in the thinned stands during the growing season of 2009 has also been reported in other studies, especially in dry regions (Defreitas and Enright, 1995;Dore et al, 2010;Grady and Hart, 2006;Zhu et al, 2009). It is clear that in regions with dry seasons, the primary control on R s rate could be soil moisture.…”
Section: The Effect Of Thinning On Soil Co 2 Efflux Ratessupporting
confidence: 66%
“…Additionally, the amount of rainfall that actually reached the soil was lower in control plots due to the higher forest crown interception during light rainfall events (Bao et al, 2004); for example, over 60% of the annual rainfall was intercepted by the pine canopy (Bao et al, 2004). Our observation of lower soil moisture and lower R s in the control stands than in the thinned stands during the growing season of 2009 has also been reported in other studies, especially in dry regions (Defreitas and Enright, 1995;Dore et al, 2010;Grady and Hart, 2006;Zhu et al, 2009). It is clear that in regions with dry seasons, the primary control on R s rate could be soil moisture.…”
Section: The Effect Of Thinning On Soil Co 2 Efflux Ratessupporting
confidence: 66%
“…Therefore, root/fine root biomass is often closely correlated with Ra (Fig. f, Lee & Jose, ; Zhu et al ., ), while soil microbial biomass, SOC, and litter mass are widely demonstrated to tightly relate with Rh (Fig. e, Yoshitake et al ., ; Iqbal et al ., ), inducing their significant correlations with Rs (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This pattern of Rs under N addition is different in N limited ecosystems, which have often been reported to increase Rs via root products and biomass [74]. Importantly, heterotrophic respiration dominates Rs (almost 72%) [75], and the positive relationships were observed between root/fine root biomass and autotrophic respiration [15,76] and microbial biomass and heterotrophic respiration [77]. Additionally, N addition significantly increased root biomass ( Figure S1) and decreased microbial biomass, which collectively suggested that heterotrophic respiration may have decreased even further under N addition.…”
Section: Correlation Between Soil Respiration and Microbial Biomass mentioning
confidence: 87%